Infancy weight gain, parental socioeconomic position, and childhood overweight and obesity: a Danish register-based cohort study - Torill Alise Rotevatn; Charlotte Overgaard; G. J. Melendez-Torres; Rikke Nørmark Mortensen; Line Rosenkilde Ullits; Anna Marie Balling Høstgaard; Christian Torp-Pedersen; Henrik Bøggild (BMC, 2019)
Abstract Background Rapid infant weight gain (RIWG) is a very strong predictor of childhood overweight and obesity (COO). Socioeconomic position (SEP) is also related to the risk of COO and parents of different SEP may differ in their reaction to accelerated infant weight gain. Together this could lead to differences in how weight gain and COO risk relate across SEP. This study aimed to analyse possible interaction of SEP and RIWG on COO risk. Methods A register-based longitudinal cohort study followed 19,894 healthy, term infants, born in Denmark between December 2011 and May 2015. Logistic regression models were used to estimate odds ratios (OR) of COO risk at 2 years (22-26 months) of age with 95% confidence intervals (95% CI) for categories of infancy weight gain based on changes in weight-for-age z-scores between 0 and 8-10 months of age (slow (<− 0.67), mean (− 0.67-0.67), rapid (> 0.67-1.34) and very rapid (> 1.34)). Possible multiplicative and additive interaction of SEP (based on household income and maternal education) on the relationship between infancy weight gain and COO were analysed. Results In total, 19.1 and 15.1% experienced rapid or very rapid weight gain, respectively, and 1497 (7.5%) children were classified with COO at follow-up. These prevalences were higher in those with lower levels of SEP. Adjusted OR for COO were 3.09 (95% CI [2.66-3.59]) and 7.58 (95% CI [6.51-8.83]) for rapid and very rapid weight gain, respectively, when household income was included in the model. Results were similar in the model including maternal education. No signs of interactions were detected on a multiplicative scale. Weak signs of additive interaction were present, but these values did not reach significance. Conclusion Both rapid and very rapid weight gain were associated with substantially higher risks of COO but these associations were not modified by SEP. This indicates that promotion of healthy weight gain should take place in all population groups irrespective of their SEP.